Kedudukan Jabatan dan Akta Pejabat Pembuat Akta Tanah dalam Perspektif Tata Usaha Negara - Cintantya, Pinahayu; Soekesi, Titik Soeryati (Universitas Negeri Malang, 2022)
This study aimed to analyze the standing over the position and the deed of the Land Deed Officer from the perspective of state administration. This study used a legal approach and a case approach. This type of research uses normative juridical research methods. The data sources used in this study were primary and secondary. The data analysis technique used a grammatical and systematic interpretation method. The study results showed that the Land Deed Officer did not carry out a unilateral state administrative, legal action in carrying out his authority. The Land Deed Official in issuing the deed was only based on the interests and initiatives of the parties, in contrast to the state administrative official who issued a decision on the authority that was in him. The deed of the Land Deed Officer could not be classified as a state administrative decision because it was not individual, concrete, and final.